Blended Learning in Teacher Profession Education (PPG) of Germany Education as The 21st Century Teacher Training Model - Dewi Kartika Ardiyani; Primardiana Hermilia Wijayati; Edy Hidayat (Journal of Development Research, 2020)
This study aims to solve problems related to the policy of Teacher Professional Development (TPD) program. This research produces a syllabus of in-office TPD for the German language to solve problems faced in the field; it is necessary to provide provision and preparation for lecturers so that the preparation and implementation of learning have the same standards and goals and the percentage of pedagogic material is more than the professional content. Meanwhile the composition of the competency test is otherwise. In this study, a new policy of TPD is formulated based on 21st century competencies and 21st century learning models that have been successfully applied in Australia, namely a life skills-based learning approach, or known as life- based learning. This framework has become the flagship program for learning innovation at the State University of Malang. The research employed a research and development method that begins with problem identification or problem formulation. The syllabus design is created and developed based on performance and needs analysis, and oriented to the principles of teacher training in the 21st century. These principles are reflected in the syllabus which contains pegadodic competences, professional competence, the ability to use digital media through blended learning and digital-based learning. Based on the results of the validation by German learning experts and suggestions from users, it can be concluded that the PPG German syllabus design is feasible to use. Nevertheless, it is necessary to refine the time allocation according to the needs and clarity of evaluation and assessment.